Analisis Pelayanan Prima pada Perusahaan Daerah Air Minum (PDAM) Tirtamangutama Kabupaten Badung (Studi Kasus : Pelanggan Golongan Industri Besar di Wilayah Kuta Utara) - Ivaliana Devi, Ni Putu Mas; Sastra Wijaya, Komang Adi; Yudharta, Putu Dharmanu (CITIZEN CHARTER, 2018)
ABSTRACT Tirtamangutama Regional Water Supply Company (PDAM) at Badung Regency is one of the regional-owned business units, which is engaged in the distribution of clean water for the general public. The problem in the implementation of the excellent service as a provider of clean water services to the customers in large industry groups is the absence of notification regarding to the reparation of PDAM pipes, which caused a large profit loss for the hotel side and there’s no response about the complaints from PDAM side. The purpose of this study is to find out how the analysis of excellent service of PDAM at the Badung Regency was conducted by studying large industrial customers in the North Kuta region. The indicators used in this study are the Excellent Service indicators from Barata (2003), namely (1). Attitudes, (2). Attention, (3). Action, (4).Ability, (5).Appearance, (6) Responsibility. This study uses descriptive qualitative method by means of data collection techniques using observation, interviews, and documentation. The results of this study indicate that the implementation of excellent service at PDAM Badung Regency is still not running optimally. This is because the PDAM has not been able to apply K3 (Quality, Quantity, Continuity) of clean water services so that most of the Large Industrial customers still use wells as the main water source. This study produced a research recommendation so that the PDAM would optimize services through the creation of customer forums, recruitment of new employees, involving the participation of the government and the community in supervising and maximizing the services to customers. Keywords : Excelent Service, Public Service, Regional Water Supply Company (PDAM)